2013
DOI: 10.1007/s10544-013-9775-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric microfluidic devices exhibiting sufficient capture of cancer cell line for isolation of circulating tumor cells

Abstract: Here, we developed polymeric microfluidic devices for the isolation of circulating tumor cells. The devices, with more than 30,000 microposts in the channel, were produced successfully by a UV light-curing process lasting 3 min. The device surface was coated with anti-epithelial cell adhesion molecule antibody by just contacting the antibody solution, and a flow system including the device was established to send a cell suspension through it. We carried out flow tests for evaluation of the device's ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…To separate CTCs from benign cells in blood, two major approaches can be used: biochemical approaches and biophysical approaches. In biochemical approaches, affinity capture of cell surface antigens (Gao et al 2013;Nagrath et al 2007;Ariyasu et al 2012;Ohnaga et al 2013;Liu et al 2013a;Sheng et al 2013) and fluorescent labeling are generally used to identify CTCs. These examples include the Veridex Cellsearch® system (Raritan, NJ, USA), which has been approved by the U.S. FDA (Food and Drug Administration) for clinical enumeration of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…To separate CTCs from benign cells in blood, two major approaches can be used: biochemical approaches and biophysical approaches. In biochemical approaches, affinity capture of cell surface antigens (Gao et al 2013;Nagrath et al 2007;Ariyasu et al 2012;Ohnaga et al 2013;Liu et al 2013a;Sheng et al 2013) and fluorescent labeling are generally used to identify CTCs. These examples include the Veridex Cellsearch® system (Raritan, NJ, USA), which has been approved by the U.S. FDA (Food and Drug Administration) for clinical enumeration of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we showed that the 'podoplanin-chip' effectively captured mesothelioma cells of another cell line, ACC-MESO-4 (15), indicating that the novel CTC-chip is a promising modality to detect some kinds of tumor cells including EpCAM-negative cells due to non-epithelial origin (e.g., mesothelioma cells) or undergoing epithelial-mesenchymal transition (EMT). Among a variety of systems for capture EpCAM-negative CTCs such as size-based or density-based separation systems (20), we employed a microfluidic system to capture CTCs called CTC-chip (14,15). The CTC-chip had been originally developed in USA (21), but the original CTC-chip can capture only EpCAM-positive CTCs because an anti-EpCAM antibody to capture CTCs is conjugated and another antibody is not available in the system.…”
Section: Discussionmentioning
confidence: 99%
“…The cell capture efficiency was represented as N-captured/N-total (14,15). The average and standard error (SE) of capture efficiency were calculated from results obtained in triplicated experiments.…”
Section: Preparation Of Ctc-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…8e&f). Antibody functionalized micropillars in microfluidic channels were utilized to increase overall surface area and to enhance target cell–surface interactions, thus improving the capture efficiency of rare CTCs from blood (Hansmann et al, 2011; Nagrath et al, 2007; Ohnaga et al, 2013). Moreover, other studies improved the cell–probe functionalized surface interactions by utilizing microposts from ultra-high porosity CNT forests (Chen et al, 2012).…”
Section: Microfluidicsmentioning
confidence: 99%